Nature. A murder of crows [videorecording (DVD)] - Fleming, Susan; Young, Nora (PBS Distribution, 2010)
New research has shown that crows are among the most intelligent animals in the world, able to use tools as only elephants and chimpanzees do, able to recognize each other's voices and 250 distinct calls. Crow experts from around the world sing their praises, and present us with captivating new footage of crows as we have never seen them before.